Análisis teórico de los sistemas de producción de cloro en sitio para la desinfección del agua (2023)
Obtaining chlorine on site, from electrolysis, is a process that has been developed since the year 1800 by the scientist William Nicholson, upon discovering that electrical energy had the ability to participate and intervene in different reactions mainly based on water. However, it is not until 1832 that the physicist and chemist Michael Faraday manages to explain, through different investigations, the quantitative relationship between the dissociated molecules and the electrical energy introduced into the system, thus giving rise to the laws of electrolysis still applied. currently